THE EFFECT OF TRANSFORMATIONAL LEADERSHIP STYLE AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT PT. BATAM OILFIELD SUPPLY SERVICES INDONESIA - Ahmad Yasin; Mira Yona; Hanafi Siregar; Latip Adlin (CV. Radja Publika, 2026)
This study aims to analyze the effect of transformational leadership style and work motivation on employee performance at PT Batam Oilfield Supply Services Indonesia. The research adopts a quantitative approach with a causal‑associative design involving a saturated sample of 100 permanent and contract employees. Data were collected using a 5‑point Likert‑scale questionnaire, whose validity was tested with item–total correlation and reliability with Cronbach’s alpha, followed by classical assumption tests and multiple linear regression analysis. The results show that transformational leadership has a positive and significant partial effect on employee performance, and work motivation also has a positive and significant partial effect; motivation demonstrates a relatively stronger standardized coefficient than leadership. Simultaneously, transformational leadership and work motivation significantly influence employee performance with an R² value of 0.590, indicating that both variables jointly explain 59.0% of performance variance, while the remaining 41.0% is affected by other factors not included in the model. These findings confirm all proposed hypotheses and underline the importance of strengthening transformational leadership practices and structured motivation systems as strategic levers for improving employee performance in high‑risk, high‑precision oilfield service operations.